Interpretations of healthy eating after a diagnosis of multiple sclerosis: a secondary qualitative analysis - Weiss, Hannah; Russell, Rebecca; Black, Lucinda; Begley, Andrea (EMERALD GROUP PUBLISHING LTD, 2023)
Purpose: Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system that causes debilitating symptoms. Currently, there is insufficient evidence to recommend a special diet for people with MS to slow disease progression and reduce symptoms. Little is known about the dietary choices made by people with MS. This study aimed to explore the interpretations of healthy eating in people recently diagnosed with MS. Objectives were to investigate the types of changes in food choices and to describe the impact of making these changes. Design/methodology/approach: A social constructionist approach applying qualitative secondary analysis of semi-structured interviews was conducted (n = 11). Interviews were transcribed, coded and analysed using a deductive approach. Findings: Participants were mostly female (82%), mean age 47 years and mean time since diagnosis eight months. Four themes emerged from the data: (1) moving in the direction of the dietary guidelines, (2) modifying intake of dietary fat, (3) requiring mental effort and (4) needing input from a dietitian. Practical implications: The directions of food choices and the absence of dietetic input highlighted in this study suggest the need for evidence-based nutrition education that enables people with MS to tailor dietary guidelines according to their preferences. Originality/value: How people interpret healthy eating advice and the impact on making food choice changes is useful for explaining dietary changes in MS. Special diets promoted for MS provide conflicting advice, and the lack of access to dietitians means that additional mental effort is required when interpreting healthy eating messages and diets.